Comparison of Optical Coherence Tomography Angiography and Laser Speckle Flowgraphy for the Diagnosis of Normal-Tension Glaucoma - Asuka Takeyama; Kyoko Ishida; Ayako Anraku; Masahiro Ishida; Goji Tomita (Journal of Ophthalmology)
Purpose. To compare optical coherence tomography angiography (OCT-A) and laser speckle flowgraphy (LSFG) for the diagnosis of normal-tension glaucoma (NTG). Methods. Twenty-eight eyes of 28 patients with NTG and 25 eyes of 25 normal subjects matched for age, refractive errors, systemic blood pressure, and central corneal thickness were evaluated. OCT-A was used to measure whole image vessel density, inside disc vessel density, and peripapillary vessel density; using LSFG, mean blur rate (MBR) inside the whole optic nerve head (ONH) area (MBRA), and MBR of the vessel area (MBRV) and tissue area (MBRT) inside the ONH, were determined. Receiver operating characteristic (ROC) curves and areas under the ROC (AUROC) were used to assess the diagnostic ability of each variable. Results. The AUROC for OCT-A whole image vessel density (0.950) was significantly greater than that for OCT-A peripapillary vessel density (0.830) and for all LSFG parameters (MBRA = 0.793, MBRV = 0.601, and MBRT = 0.61) (P<0.001). The AUROC for OCT-A inside disc vessel density (0.931) was significantly greater than that for all LSFG parameters (P<0.005). Conclusions. OCT-A vessel density had a higher glaucoma diagnostic ability compared to all LSFG parameters in patients with NTG.